The Rastakhiz Party and Pahlavism: the beginnings of state anti-Westernism in Iran. Issue 2 (15th March 2018) - Shakibi, Zhand
Abstract: The historiography of Pahlavi Iran has been unduly influenced, in the words of Cyrus Schayegh, by 'a methodological statist' paradigm based on the assumption that the state, dominating society, strove to implement radical Westernization while society's role was passive and reactive—and that society did not exercise substantial influence on Pahlavi policy-making, in particular during the period covered here, 1967–1979. Consequently, a large gap between state and society emerged and in 1979 the monarchy was overthrown. This article argues that this paradigm needs revision given its inadequate attention to the changes the shah made in the state's discourses on Westernization and Iranian authenticity and national identity in response to a growing societal and intellectual backlash to Pahlavi Westernization. The Rastakhiz Party and its publications played the key role in this emerging Pahlavi anti-Westernism. The article shows that these changes were more substantial and impactful on the state's discourses on national identity and the West than has been assumed by existing literature.